PLANTS COMMUNITIES OF VASCULAR PLANTS OF MAINLAND PORTUGAL, AZORES AND MADEIRA - Costa, José (2012)
In this paper we mean the 830 associations, 239 alliances, 116 orders, and 63 phyosociological class presents on Portugal, Azores, and Madeira Islands, we mention also the 65 subaliances, 2 suborders and 4 subclasses. The higher syntaxa to subaliance have succint description, and the characteristics species are related. The new syntax and corrections are described and listed in an annex, also presents a floristic catalog sheet which syntaxonomical states of the taxa.